Undernourishment Needs Overemphasis: Lived Experiences of Elementary Teachers and Parents Having Undernourished Schoolchildren - Cuba, Avril Alys; Albina, Albert; Jamandron, Novie John; Sartin, Edielyn; Rivera, Jake Patrick (Jurnal Gizi dan Pangan, 2023)
This present study aimed to explore the lived experiences of parents and elementary teachers with undernourished children or pupils. These pupils are enrolled in two elementary schools in the 4th District of Santa Catalina under the Division of Negros Oriental, Philippines. Employing the descriptive phenomenological design through the unstructured in-depth interview method on the experiences of teachers and parents with undernourished schoolchildren, twelve participants agreed to participate in this study. Digitally recorded interviews were thematically analyzed to generate the themes and subthemes. We generated four themes: (a) pupils' poor class performance and behavior; (b) teachers' strategic initiative aimed at enhancing performance and behavior; (c) Department of Education’s (DepEd) support for pupils' well-being; and (d) children's poor eating behavior. Teachers were challenged in handling pupils who are undernourished as the latter becomes mentally and physically absent in the classroom. To ensure that these pupils are not left behind, teachers make some interventions, like peer tutoring, to help the pupils cope with every day’s lesson. With the intention of improving the nutritional status of undernourished pupils, schools implemented the school-based feeding program and the giving of nutritious foods that may be brought home for pupils’ breakfast or supper. We conclude that despite the challenges encountered, teachers and parents devise interventions to lessen the negative effects of undernutrition with the help of DepEd.